Violência e tráfico: o indizível e o impronunciável - cenas de Campinas, Rio de Janeiro e São Paulo - Almendra, Carlos Alberto da Cunha (2007)
The agony and the insecurity generated by the violence can not be solved exclusively by the police presence, or purely and simply for the truculent and intimidated action of the police agent. We need to abandon repressive and punitive practical considered inefficient and not capable, in favor of more effectiveness actions that privilege the distributive system of properties, opportunities and power. Impunity of the delicts needs to be finished. According to this perspective, in Campinas Metropolitan Region we are going to note an urban growth completely disordered (particularly in the peripheric poor regions, where clandestine occupations, land divisions and slum quarters represent the commoner format), unemployment of the poorest part of the population and the smaller level of education, exaggerated concentration of the rich people in the hands of a small part of the population (creating a social contrast extremely accentuated), lack of assistencial and urban structure that reaches a great part of the poorest peripheric population (point of convergence (meeting) of various highways), complemented with a high acquisitive power (in terms of Brazil) of the population. These factors, in its conjunct, become the Region an attraction center of violence and criminality. In Campinas Metropolitan Region, the Organized Crime, particularly that dedicated branch to the traffic of drugs and weapons find a lucus extremely favorable, because the region is rich and crossing point of important highways connecting to the coast an the North to the South of the country, having penitentiary complexes, besides being a pioneer area o PCC (First Command of The Capital) actuations, presents hegemonic in all its area inside and outside of the penitentiaries. The word of the Traffic in the Region presents similar characteristics of the ones found in Sao Paulo than in Rio de Janeiro. The geographic configuration represented by the relief, better transit condition in Campinas peripheral areas, facilitates the escapement of the trafficker ant the blitz moments. We don t find in the Region serious rivalries among factions because the hegemony was conquered by the PCC, that acts much more as a franchise firm, asking for the associated traffickers protection and logistic support (supplying weapons, vehicles and judicial protection as the dono of areas or boca de trafico . They act inside an eminently enterprise structure, the reason why it will have to be more studied by the economists inside a Criminal Economy . It doesn t exist a clear assistance by outlaws in relation to the population because the Silent Law is more guaranteed by the violence than by the relations of complicity, assistance and protection. About all the other characteristics, proper of the organization of the space by the Traffic, we are going to find them in the Campinas Metropolitan Region, since is an area of important influence of the city of Sao Paulo, the reason why any public politics of combat and prevention to the violence and criminality will have to be, before everything, integrated with similar politics for all there regions. If urgent measures were not adopted to try to control the violence and the criminality in the Region, in few year we will have situations extremely complicated for life quality, crack seems to be the drug that is going to have terrify increase, especially with the presence of the super-crack cheaper and devastator